206k views
15 votes
Given

log_(2)(x) = (3)/( log_(xy)(2) )
express y in terms of x​

1 Answer

6 votes

Answer:


\displaystyle y = x^{-(2)/(3)}

Explanation:

Logarithms

Some properties of logarithms will be useful to solve this problem:

1.
\log(pq)=\log p+\log q

2.
\displaystyle \log_pq=(1)/(\log_qp)

3.
\displaystyle \log p^q=q\log p

We are given the equation:


\displaystyle \log_(2)(x) = (3)/( \log_(xy)(2) )

Applying the second property:


\displaystyle \log_(xy)(2)=(1)/( \log_(2)(xy))

Substituting:


\displaystyle \log_(2)(x) = 3\log_(2)(xy)

Applying the first property:


\displaystyle \log_(2)(x) = 3(\log_(2)(x)+\log_(2)(y))

Operating:


\displaystyle \log_(2)(x) = 3\log_(2)(x)+3\log_(2)(y)

Rearranging:


\displaystyle \log_(2)(x) - 3\log_(2)(x)=3\log_(2)(y)

Simplifying:


\displaystyle -2\log_(2)(x) =3\log_(2)(y)

Dividing by 3:


\displaystyle \log_(2)(y)=(-2\log_(2)(x))/(3)

Applying the third property:


\displaystyle \log_(2)(y)=\log_(2)\left(x^{-(2)/(3)}\right)

Applying inverse logs:


\boxed{y = x^{-(2)/(3)}}

User Sea Coast Of Tibet
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.